(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the present investigation, approximately 6219 metric tons (MT) of waste were generated from various point sources in Sangola city during the year 2018-19. The largest volume of waste, about 3243 MT, was debris, contributing 52% of the total solid waste generated. Cattle waste (dung) accounted for 24%, while municipal solid waste (MSW) from collection centers also contributed 24%. The local festivals in Sangola during February and March significantly increased waste generation due to large gatherings, food stalls, decorations, and other activities. This period saw higher average cow dung generation, with 25.5 MT in February and 23.3 MT in March. Efficient management practices, such as timely collection and processing of cow dung into compost or biogas, are crucial during these months. The monsoon rains in June and July led to reduced market and outdoor activities, resulting in lower waste generation, reflected in the decreased debris (225 MT in June, 222 MT in July) and total MSW (417 MT in June, 438 MT in July). These findings highlight the need for adaptive and effective waste management strategies to handle the varying quantities and types of waste generated throughout the year, ensuring sustainable development and a healthier environment for Sangola city.